Air pollution monitoring system for smart city - Khan, Md. Hasib Bin Hossain; Rahman, Raihan Ur; Arafat, Md. Yeasin; Jony, M. A. Nayem (BRAC Univeristy, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.